1999
DOI: 10.1016/s0895-7061(99)00064-3
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium supplementation attenuates, but does not prevent, development of hypertension in spontaneously hypertensive rats

Abstract: This study evaluated the effects of magnesium supplementation on the development of hypertension in spontaneously hypertensive rats (SHR) and assesses the actions of magnesium on extracellular and intracellular Ca2+, Na+, and K+ status. Ten-week-old SHR (n = 72) and Wistar-Kyoto rats (WKY) (n = 60) were divided into four groups: WKY, Mg-WKY (WKY receiving 650 mg/L Mg(2+)supplementation), SHR, and Mg-SHR (SHR receiving Mg2+). Rats were studied for 17 weeks. Serum and erythrocyte Mg2+ and Ca2+ (measured by atomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
28
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 42 publications
5
28
0
Order By: Relevance
“…The CLDN16 phosphorylation may play an important role under physiological and pathophysiological conditions. Blood pressure is inversely associated with body Mg 2ϩ levels (39), and dietary Mg 2ϩ supplementation suppresses the development of hypertension (40). The phosphoserine level of CLDN16 has been shown to decrease in Dahl salt-sensitive hypertensive rats, which suggests that Mg 2ϩ reabsorption was mediated via CLDN16 to be reduced in hypertensive rats (19).…”
Section: Discussionmentioning
confidence: 99%
“…The CLDN16 phosphorylation may play an important role under physiological and pathophysiological conditions. Blood pressure is inversely associated with body Mg 2ϩ levels (39), and dietary Mg 2ϩ supplementation suppresses the development of hypertension (40). The phosphoserine level of CLDN16 has been shown to decrease in Dahl salt-sensitive hypertensive rats, which suggests that Mg 2ϩ reabsorption was mediated via CLDN16 to be reduced in hypertensive rats (19).…”
Section: Discussionmentioning
confidence: 99%
“…87- 89 Magnesium supplementation has been shown to lower blood pressure in some experimental models of hypertension. 90, 91 Clinical studies have shown increased, decreased and no effect of Mg 2+ depletion or supplementation in hypertension. Despite these inconsistencies there are some groups of hypertensive patients who consistently demonstrate altered Mg 2+ metabolism.…”
Section: Trpm7 Mg 2+ and Hypertensionmentioning
confidence: 99%
“…Magnesium has been the subject of experimental and clinical studies in hypertension [4][5][6][7][8] on the background that epidemiological studies showed significant inverse correlation between serum magnesium levels and incidence of cardiovascular disease [9] [10,11].…”
Section: Introductionmentioning
confidence: 99%